Resolving Human Rights Violation Cases in Aceh, Indonesia - Matondang, Ikhwan; Afrinal, Afrinal; Khalida, Azhariah; Fatia, Azhariah; Amin, Saifuddin (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
This study aimed to examine the position and role of Ulama in resolving human rights violation cases by the Aceh Truth and Reconciliation Commission (TRC). It analyzed the ulama representations within the Aceh TRC commissioners, their role in reconciliation, and factors that influence the role of the ulama. Data were obtained through interviews and documentation and analyzed using the Miles and Huberman model. The results showed that the ulama’s role was dismissed in cases of human rights violations. TRC's commissioners did not represent Ulama or play a significant role in the reconciliation process. Their diminished role in conflict resolution relates to delegitimization in Aceh. It occurred due to the scarcity of qualified ulama to solve the conflict and friction or polarization among them. Other causes were the ulama’s lack of attention to human rights issues and the emergence of new actors that took over their conflict resolution roles. Ulama in Aceh could reaffirm its role in conflict resolution by restoring its legitimacy. They must improve their quality and formation based on day ah, strengthen their unity, avoid friction and polarization, and maintain neutrality. Ulama should also increase their involvement in conflict resolution and human rights issues.